1983
DOI: 10.1002/jlac.198319830413
|View full text |Cite
|
Sign up to set email alerts
|

Mehrstufige, reversible Redoxsysteme, XXXII. Pyridylsubstituierte Cyclobutanderivate: Synthese und Redoxreaktionen von Cyaninen sowie Cyclobutenen und ihren Ringöffnungsprodukten

Abstract: Die Bis(pyridinium)cyclobutane 1 und 3 gehen im basischen Medium durch Luftoxidation in die blauen Cyanine 2 und 4 iiber. Methylierung von 4 fiihrt zum Cyanin 6, das sich auch aus dem Tetrakis(pyridinium)cyclobutan 5 durch oxidative Deprotonierung bildet. 6 steht in einer Natriumethanolat-Losung mit dem ,,Quadratsaurederivai" 14 im Gleichgewicht. Durch Protonierung entsteht aus 6 das Cyclobuten cis-13, das basenkatalysiert in fruns-13 ubergeht. Elektrocyclische Ringoffnung verwandelt stereoselektiv cis-13 in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Comparison to the [4]Radialene Analogue. Two [4]radialene analogues of 1 0 have been previously synthesized and studied electrochemically; they are pictured as 2 0 in Figure , with R = CH 3 or CO 2 CH 2 CH 3 . Cyclic voltammetry showed that 2 0 (R = CO 2 CH 2 CH 3 ) can be oxidized in one reversible, two-electron step to the dication 2 2+ and then in two reversible, one-electron steps to 2 3+ and 2 4+ . Similarly, the R = CH 3 version of 2 0 can be reversibly oxidized in a single two-electron step to 2 2+ , but its oxidation to 2 3+ is irreversible.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison to the [4]Radialene Analogue. Two [4]radialene analogues of 1 0 have been previously synthesized and studied electrochemically; they are pictured as 2 0 in Figure , with R = CH 3 or CO 2 CH 2 CH 3 . Cyclic voltammetry showed that 2 0 (R = CO 2 CH 2 CH 3 ) can be oxidized in one reversible, two-electron step to the dication 2 2+ and then in two reversible, one-electron steps to 2 3+ and 2 4+ . Similarly, the R = CH 3 version of 2 0 can be reversibly oxidized in a single two-electron step to 2 2+ , but its oxidation to 2 3+ is irreversible.…”
Section: Resultsmentioning
confidence: 99%